Microbial Growth and Biogenic Amine Production in a Balkan-Style Fresh Sausage during Refrigerated Storage under a CO2-Containing Anaerobic Atmosphere: Effect of the Addition of Zataria multiflora Essential Oil and Hops Extract - Diego E. Carballo; Javier Mateo; Sonia Andrés; Francisco Javier Giráldez; Emiliano J. Quinto; Ali Khanjari; Sabina Operta; Irma Caro (MDPI AG, 2019)
Fresh sausages are highly perishable, and the preservatives allowed in these types of meat preparations are limited. Balkan-style fresh sausages were prepared in triplicate without antimicrobials (Control), with an aqueous hops extract (30 mL/kg), with Zataria multiflora Boiss essential oil (1 mL/kg), or a combination of both (15 and 0.5 mL/kg, respectively), and refrigerator-stored under a 20% CO2 and 80% N2 atmosphere. The spoilage microbial growth, i.e., lactic acid bacteria (LAB), Brochothrix thermosphacta, Enterobacteriaceae, Micrococcaceae, molds and yeasts, the pH value, and the production of biogenic amines in the sausages were monitored weekly and compared with a control sausage during a 35-day storage period. Furthermore, 349 colonies of presumptive LAB (isolated from the De Mann, Rogose-Sharpe agar plates) were identified using a MALDI-TOF-based method. Growth levels to ≈ 9 Log colony forming units (CFU) per g were reached by LAB, with a predominance of Lactobacillus sakei. Enterobacteriaceae and B. thermosphacta also showed significant growth (up to 6 Log CFU/g). Biogenic amine levels increased, and tyramine values overcame 250 mg/kg. The study could not demonstrate a significant effect of antimicrobial source treatments in any of the characteristics studied, and thus, the shelf-life of sausages.